STRENGTHENING STUDENT CHARACTER EDUCATION IN JUNIOR HIGH SCHOOL - Wahyuni, Sri (Tadrib: Jurnal Pendidikan Agama Islam, 2023)
Character education is something that is very important to carry out in everyday life both in the school environment and in society. If character education does not go well, it will cause problems for students. problems related to the declining character of students is evident from the records of the Indonesian Child Protection Commission (KPAI). During the Covid-19 pandemic, the world of education experienced a lot of learning loss and a decline in student character, including many students who did not do the assignments given by the teacher, did not greet each other between students and teachers, denied the advice given by the teacher, were not disciplined in learning, and etc. This study uses qualitative research using data collection techniques of observation, interviews, and documentation. The data were then analyzed by combining the Creswell model and Mathew and Hubermen, namely by performing three stages namely, data reduction (data reduction), data display (date display) / description, and interpretation/verification of data. To check the validity of the data, triangulation, member checking and extension of the observation were carried out The results of the study show that the forms of strengthening character education at Indralaya 1 Public Middle School include class, school culture, and community-based. The teacher's role in strengthening student character education at Indralaya 1 Public Middle School includes: as a learning manager, role model, facilitator, evaluator, and counselor. Factors that influence the strengthening of character education include: a) internal factors, including instincts, will, customs/habits, conscience, and heredity b) external factors, including schools and society